Synthesis and fungicidal activity of N-thiazol-4-yl-salicylamides, a new family of anti-oomycete compounds. Issue 9 (1st May 2015) - Sulzer-Mosse, Sarah; Cederbaum, Fredrik; Lamberth, Clemens; Berthon, Guillaume; Umarye, Jayant; Grasso, Valeria; Schlereth, Alexandra; Blum, Mathias; Waldmeier, Rita
Graphical abstract: Abstract: A novel class of experimental fungicides has been discovered, which consists of special N -thiazol-4-yl-salicylamides. They originated from amide reversion of lead structures from the patent literature and are highly active against important phytopathogens, such as Phytophthora infestans (potato and tomato late blight), Plasmopara viticola (grapevine downy mildew) and Pythium ultimum (damping-off disease). Structure–activity relationship studies revealed the importance of a phenolic or enolic hydroxy function in the β-position of a carboxamide. An efficient synthesis route has been worked out, which for the first time employs the carbonyldiimidazole-mediated Lossen rearrangement in the field of thiazole carboxylic acids.